"There is no normal": how Ms. Marvel constitutes U.S. American citizenship between comics and screen - Bowar, Kyra, author; Anderson, Karrin, advisor; Marx, Nick, committee member; Martey, Rosa, committee member (Colorado State University. Libraries, 2024)
In 2014, a new superhero crashed into the Marvel Comics universe; Kamala Khan, a Muslim Pakistani American superheroine, took on the heroic mantle of "Ms. Marvel." Then, in 2022, Kamala's story was adapted to the screen as a part of Disney's Marvel Cinematic Universe. Ms. Marvel's story is one of intersections, tensions, and navigating identity in a contemporary, multicultural America. To understand how Marvel and Disney constitute U.S. American citizenship and identity, this thesis compares two versions of Kamala Khan's superhero origin story: the Marvel comic, Ms. Marvel: No Normal (2014), and its streaming television show adaptation on Disney+, Ms. Marvel (2022), produced by Disney's Marvel Studios. Pairing rhetorical criticism with media industry analysis, I argue that, through their adaptation of Ms. Marvel to the screen, Disney widens the borders around U.S. American sociocultural belonging enough to incorporate intersectionally marginalized identities without fully displacing hegemonic understandings of U.S. American citizenship. This thesis demonstrates the utility of multi-methodological critical analysis and expands the theory of constitutive rhetoric by demonstrating how one text can interpellate audience members differently. My analysis also illustrates the continued relevance of superhero media as exemplars of identity formation in contemporary culture.
There is no normal: how Ms. Marvel constitutes U.S. American citizenship between comics and screen
Keywords: citizenship; Marvel; superheroes; Disney; American identity; rhetoric